The role of central serotonin neurons and 5-ht heteroreceptor complexes in the pathophysiology of depression: A historical perspective and future prospects - Borroto-Escuela, Dasiel O.; Ambrogini, Patrizia; Chruścicka, Barbara; Lindskog, Maria; Crespo-Ramirez, Minerva; Hernández-Mondragón, Juan C.; Perez de la Mora, Miguel; Schellekens, Harriët; Fuxe, Kjell (MDPI, 2021)
Serotonin communication operates mainly in the extracellular space and cerebrospinal fluid (CSF), using volume transmission with serotonin moving from source to target cells (neurons and astroglia) via energy gradients, leading to the diffusion and convection (flow) of serotonin. One emerging concept in depression is that disturbances in the integrative allosteric receptor–receptor interactions in highly vulnerable 5-HT1A heteroreceptor complexes can contribute to causing major depression and become novel targets for the treatment of major depression (MD) and anxiety. For instance, a disruption and/or dysfunction in the 5-HT1A-FGFR1 heteroreceptor complexes in the raphe-hippocampal serotonin neuron systems can contribute to the development of MD. It leads inter alia to reduced neuroplasticity and potential atrophy in the raphe-cortical and raphe-striatal 5-HT pathways and in all its forebrain networks. Reduced 5-HT1A auto-receptor function, in-creased plasticity and trophic activity in the midbrain raphe 5-HT neurons can develop via agonist activation of allosteric receptor–receptor interactions in the 5-HT1A-FGFR1 heterocomplex. Addi-tionally, the inhibitory allosteric receptor–receptor interactions in the 5-HT1AR-5-HT2AR isorecep-tor complex therefore likely have a significant role in modulating mood, involving a reduction of postjunctional 5-HT1AR protomer signaling in the forebrain upon activation of the 5-HT2AR pro-tomer. In addition, oxytocin receptors (OXTRs) play a significant and impressive role in modulating social and cognitive related behaviors like bonding and attachment, reward and motivation. Pathological blunting of the OXTR protomers in 5-HT2AR and especially in 5-HT2CR heteroreceptor complexes can contribute to the development of depression and other types of psychiatric diseases involving disturbances in social behaviors. The 5-HTR heterocomplexes are novel targets for the treatment of MD.
Keywords: Depresión; Serotonina - Receptores; G protein-coupled receptors; Heteroreceptor complexes; Serotonin receptor; Oligomerization; Oxytocin receptor; Depression